Comparison of Media Framing and Sentiment towards Palestinian vs Rohingya Refugees: Analysis using Deep Learning Methods - Fadillah, Ahmadi; T, Fauzia G. Cempaka; Afifuddin, Mochammmad (PT FORMOSA CENDEKIA GLOBAL, 2025)
The differences in media framing and public sentiment regarding the discourse on the acceptance of Palestinian refugees by the Indonesian Government versus the presence of Rohingya refugees in Aceh reflect biases that can influence public perceptions, which in turn can have an impact on social and political stability in Indonesia in the future. This research aims to compare media framing and public sentiment towards Palestinian and Rohingya refugees using the deep learning method, a sentiment analysis technique based on NLP (Natural Language Processing) in order to gain deeper insight into the influence of the media on public perception. This research analyzes framing patterns and sentiments from news articles and social media related to Palestinian and Rohingya refugees. Media framing theory and sentiment analysis are used to understand how the media can influence public perceptions and attitudes. Deep learning methods enable deeper and more accurate analysis of large and complex text data. The expected result is an analysis of significant differences in media framing and public sentiment towards the two refugee groups. A better understanding of how the media influences public perceptions of Palestinian and Rohingya refugees can help in designing more inclusive and harmonious policies, the ultimate goal of which is to maintain social and political stability in Indonesia, considering that the country has a large and diverse Muslim population that plays an active role in in international humanitarian issues.